1978
DOI: 10.1017/s0043174500050190
|View full text |Cite
|
Sign up to set email alerts
|

Control of Yellow Nutsedge(Cyperus esculentus)and Other Weeds Before Summer Planting of Alfalfa(Medicago sativa)

Abstract: After land was plowed in the spring and prepared for planting, yellow nutsedge(Cyperus esculentusL.) was allowed to develop to heights of 10 to 12 and 20 to 25 cm. Either glyphosate [N-(phosphonomethyl)glycine] or paraquat (1,1′-dimethyl-4,4′-bipyridinium ion) was applied to emerged yellow nutsedge and other annual weeds at rates of 0.5, 1, 2, and 4 kg/ha. Half of the plots were double-disked 3 days after herbicide applications, and then all plots were planted with alfalfa(Medicago sativaL. ‘Cayuga’). Disking … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1997
1997
2003
2003

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Without competition from a crop, yellow nutsedge populations increased, even under intensive weed management in fallow areas using shallow tillage and glyphosate [N-(phosphonomethyl) glycine]. The inability to GA, 1990GA, -1994 Time of Rate application (kg ha-1) Chemical name control yellow nutsedge in fallow plots contradicts previous studies that showed reductions in yellow nutsedge densities with frequent shallow tillage Linscott et al 1978;Stoller et al 1972;Thomas 1969;Thullen and Keeley 1975). Thullen and Keeley (1975) depleted yellow nutsedge tuber carbohydrate reserves by tilling at 4-wk intervals, whereas the soil was tilled in our study at 2-mo intervals during the growing season.…”
Section: Weed Densitiesmentioning
confidence: 93%
“…Without competition from a crop, yellow nutsedge populations increased, even under intensive weed management in fallow areas using shallow tillage and glyphosate [N-(phosphonomethyl) glycine]. The inability to GA, 1990GA, -1994 Time of Rate application (kg ha-1) Chemical name control yellow nutsedge in fallow plots contradicts previous studies that showed reductions in yellow nutsedge densities with frequent shallow tillage Linscott et al 1978;Stoller et al 1972;Thomas 1969;Thullen and Keeley 1975). Thullen and Keeley (1975) depleted yellow nutsedge tuber carbohydrate reserves by tilling at 4-wk intervals, whereas the soil was tilled in our study at 2-mo intervals during the growing season.…”
Section: Weed Densitiesmentioning
confidence: 93%